2013
DOI: 10.1093/esr/jct013
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of Nationalist Attitudes: Domestic Music Listening, Participation in National Celebrations, and Far Right Voting

Abstract: In this contribution, we aim to develop an understanding of the behavioural manifestations of nationalism. Building on social identity theory and ethnic competition theory, we examine to what extent nationalist attitudes and perceived cultural ethnic threat are related to domestic music listening, participating in national celebrations and commemorations and voting for far right parties. We use data from the Social and Cultural Developments in The Netherlands surveys (SOCON, wave 2007). We find that the strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…The question is, however, whether such national ceremonies indeed have the power to increase feelings of national belonging. While previous studies have demonstrated that participation in national commemorations and feelings of national belonging are positively related (Lubbers and Meuleman 2016;Meuleman and Lubbers 2013), we cannot automatically conclude that participation in itself increases feelings of national belonging. Issues such as self-selection make it difficult to draw conclusions on whether or not participation in itself is the cause of enhanced feelings of national belonging (Etzioni 2000).…”
Section: Introductioncontrasting
confidence: 74%
See 4 more Smart Citations
“…The question is, however, whether such national ceremonies indeed have the power to increase feelings of national belonging. While previous studies have demonstrated that participation in national commemorations and feelings of national belonging are positively related (Lubbers and Meuleman 2016;Meuleman and Lubbers 2013), we cannot automatically conclude that participation in itself increases feelings of national belonging. Issues such as self-selection make it difficult to draw conclusions on whether or not participation in itself is the cause of enhanced feelings of national belonging (Etzioni 2000).…”
Section: Introductioncontrasting
confidence: 74%
“…Many studies have also empirically demonstrated that participation in national commemorations and feelings of national belonging are positively related (Lubbers and Meuleman 2016;Meuleman and Lubbers 2013). We are uncertain, however, about the direction of this relationship (Coopmans, Lubbers, and Meuleman 2015;Etzioni 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations